Psychometric properties of the earthquake knowledge questionnaire: Development for the Persian population - Leila Jahangiry; Javad Babaei; Mitra Baghaeian; Hosna RashidiBirgani; Neda Gilani (PLoS ONE, 2025)
Background Disaster management, as defined by the United Nations Office for Disaster Risk Reduction (UNDRR) involves foresighted planning to prevent, prepare for, respond to, and recover from disasters. Research proves that earthquake knowledge significantly contributes to preparedness behavior. The aim of this research is to develop a psychometrically valid questionnaire following UNDRR guidelines to assess earthquake awareness. Method An exploratory sequential mixed-methods study was conducted between April and July 2024 in Tabriz, Iran. In the initial phase of the study, a comprehensive literature review and qualitative research were conducted to develop a preliminary item pool related to earthquake knowledge. Subsequently, the face validity, content validity, and construct validity of the items were assessed, followed by an evaluation of reliability through internal consistency, McDonald’s omega and test-retest methods. Exploratory Factor Analysis (EFA) using polychoric correlations and parallel analysis was conducted to determine factor structure. A polychoric correlation matrix was estimated from the sample of 350 respondents with 1000 iterations and using the principal factors method. Results A polychoric correlation matrix was computed in R software (version 4.4.1) to estimate the non-linear relations between 14 ordinal items of the earthquake knowledge scale, of a sample of 350 participants. Parallel analysis using principal axis factoring determined three factors with adjusted eigenvalues greater than zero (observed eigenvalues: 7.5, 1.8, and 1.2 for the first, second, and third factor, respectively), which were retained as significant. The 14-item earthquake knowledge questionnaire (14-EKQ) was organized into three factors: Geological Knowledge, Mitigation Measures, and Preparedness Knowledge, reflecting various dimensions of earthquake awareness. EFA revealed that these three factors collectively accounted for 83.6% of the total variance. The RMSEA value of (RMSE = 0.070) falls within the acceptable range (≤ 0.08), indicating a reasonable fit. The CFI (CFI = 0.916) value is close to the threshold of 0.95, indicating a relatively good fit. The TLI value (TLI = 0.908) is slightly below the threshold of 0.95 but still suggests an acceptable fit. The internal consistency and internal correlation coefficient of EKQ indicated acceptable reliability. Conclusion This study successfully developed and validated a 14-item EKQ. The scale was organized into three distinct factors: Geological knowledge, Mitigation measures, and preparedness knowledge, which collectively accounted for 83.6% of the total variance, demonstrating strong explanatory power. The use of polychoric correlation matrices, parallel analysis, and principal axis factoring (PAF) improved the factor extraction process by appropriately accounting for the ordinal nature of the questionnaire data. Model fit indices, including RMSEA and TLI, indicated an acceptable to good fit of the scale to the data. Additionally, the scale demonstrated acceptable reliability, as evidenced by internal consistency measures, McDonald’s omega, and test-retest reliability. The study’s EKQ makes a significant contribution to earthquake education by providing a validated tool to assess public awareness across geological knowledge, mitigation strategies, and preparedness knowledge, aligning with UNDRR guidelines. Further research is recommended to confirm its generalizability across diverse populations and contexts.